INOVASI PEMBELAJARAN AKUNTANSI BERBASIS BLENDED LEARNING - Latifah, Lyna; Susilowati, Nurdian (Fakultas Ekonomi, Universitas Negeri Semarang, 2011)
the accounting lectures have a big challengeb to improve the quality of graduates who are expected to have high knowledge and skill, to have good critical analysis and decision making. Thus: accounting lecturers are needed to improve their teaching and learning processes especially on learning design and assessment. Improving students knowledge and skill in accounting field can be created by using learning philosophy which makes students active and integrative in the class room. this articles discusses about the innovation of accounting learning with blended learning which collaborates cooperative learning and e-learning. Cooperative learning is a learning approach which emphasizes on structured behavior to cooperate in groups it can improve students interpersonal skill, cooperation, critical analysis and decision making. On the other hand, the application of cooperative learning needs more time so it can be solved by using computer with e-learning.